Impact of good governance in the economic development of Western Balkan countries - Engjell Pere (European Journal of Government and Economics (EJGE), 2015)
After the socio-economic transformation and the establishment of the free market institutions, the development and improvement of living standards in post transition economies are deemed to depend more and more on the so called secondary "generating" reforms, at the core of which is the good governance. Drawing from this approach, this article seeks to address the role and the effect of the good governance in the economic development of the Western Balkans countries. More specifically, the article investigates the impact of good governance in the rates of economic growth of GDP. The article adopts a quantitative methodology approach, i.e. an econometric model based on the examination of a panel - data of good governance indicators for Western Balkans countries for the period 1996 - 2012. The analysis concentrates on the following Western Balkan Countries: Albania, Bosnia and Herzegovina, Croatia, Kosovo, Macedonia, Montenegro and Serbia.
Keywords: 330; Western Balkans; good governance; economic growth; governance index.